Fracture and dislodgment of a guidewire retrieved by a Solitaire AB neurovascular remodeling device - Liu, Zhengli; Zhao, Boxiang; He, Xu; Gu, Jianping; Gong, Maofeng; Kong, Jie (Frontiers in Materials, 2023)
Background: Fracture and dislodgment of a guidewire are very rare, but they often cause serious complications. Method: In this case, a case was reported where part of the guidewire was blocked to the posterior tibial. We tried to remove it by Solitaire AB Neurovascular Remodeling Device. Result: Solitaire AB Neurovascular Remodeling Device was successfully used to remove the fracture and dislodgment of a guidewire. Conclusion: After the guidewire is fractured, the Solitaire AB can be used to remove it, which can be used as a simple and effective method to reduce complications.